2015
DOI: 10.18632/oncotarget.6706
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the FGFR2 mesenchymal splicing variant in epithelial cells drives epithelial-mesenchymal transition

Abstract: The FGFRs are receptor tyrosine kinases expressed by tissue-specific alternative splicing in epithelial IIIb or mesenchymal IIIc isoforms. Deregulation of FGF/FGFR signaling unbalances the epithelial-stromal homeostasis and may lead to cancer development. In the epithelial-context, while FGFR2b/KGFR acts as tumor suppressor, FGFR2c appears to play an oncogenic role. Based on our recent observation that the switching of FGFR2b versus FGFR2c induces EMT, here we investigated the biological outcome of the ectopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(117 citation statements)
references
References 50 publications
(82 reference statements)
5
108
2
Order By: Relevance
“…As a consequence of the initiation of a pathological cancer‐associated type III EMT process driven by the ectopic expression of FGFR2c in normal human keratinocytes, we have also recently described that the mesenchymal‐like morphology, actin reorganization, and modulation of EMT markers led to invasiveness and anchorage‐independent growth of the cells . These interesting observations prompted us to further investigate the behaviour of our cell model of keratinocytes, ectopically expressing the mesenchymal FGFR2c variant, during in vitro differentiation and stratification and in comparison with cells endogenously expressing or overexpressing by transfection the epithelial FGFR2b isoform.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…As a consequence of the initiation of a pathological cancer‐associated type III EMT process driven by the ectopic expression of FGFR2c in normal human keratinocytes, we have also recently described that the mesenchymal‐like morphology, actin reorganization, and modulation of EMT markers led to invasiveness and anchorage‐independent growth of the cells . These interesting observations prompted us to further investigate the behaviour of our cell model of keratinocytes, ectopically expressing the mesenchymal FGFR2c variant, during in vitro differentiation and stratification and in comparison with cells endogenously expressing or overexpressing by transfection the epithelial FGFR2b isoform.…”
Section: Introductionmentioning
confidence: 76%
“…All assays included a negative control and were replicated three times. The thermal cycling program was performed as described . Real‐time quantitation was performed with the help of the iCycler IQ optical system software version 3.0a (Bio‐Rad), according to the manufacturer's manual.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, when we considered “incoming” signals to malignant cells, we found that CAFs expressed notably higher numbers of ligands that correspond to receptors expressed by the malignant cells of the corresponding tumor (hypergeometric test, p<0.05; Figures 4E and S5L). These included interactions that may promote EMT, such as TGFB3-TGFBR2, FGF7-FGFR2 and CXCL12-CXCR7 (Figure 4F) (Moustakas and Heldin, 2016; Ranieri et al, 2016; Yao et al, 2016). Accordingly, when we stained tumors for CAF markers (FAP, PDPN), we found that CAFs were present near p-EMT cells at the leading edge (Figures 4C and S5M).…”
Section: Resultsmentioning
confidence: 99%
“…The exon 9-containing isoform, which is known as the IIIc isoform, recognizes FGF-2 and is expressed in mesenchymal cells. Moreover, the expression of the IIIc isoform in various types of human cancer has been linked to epithelial to mesenchymal transition (EMT) and increased invasiveness, metastatic potential and cancer stem cell self-renewal 9, 10 . Our studies have shown that Akt3, and secondarily Akt1, transduce signals that shift the alternative splicing of FGFR-2 toward the IIIc isoform, which is recognized by FGF-2.…”
Section: Introductionmentioning
confidence: 99%